2019
DOI: 10.29121/granthaalayah.v7.i2.2019.995
|View full text |Cite
|
Sign up to set email alerts
|

Stock Price Movement and Volatility in Muscat Security Market (Msm)

Abstract: This paper examines the stock price movement and volatility in listed financial Omani Companies in MSM. The study made use of secondary data. This study is an attempt to answer these important questions, is there an effect of the announcement of the dividend policy on the market value of the shares of the Omani companies listed in MSM? Moreover, Is there any effect for each of the announcement of the earnings per share and distribution of profits on the market value of the shares of the Omani companies listed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Many researchers have scrutinized the role of government expenses on the EG of the country (Aziz & Asadullah, 2017). However, the literature still lacks an efficient explanation of GE’s different dimensions on the EG in Oman’s particular context (Castaño et al, 2016; Husain & Javed, 2019a, 2019b; Husain et al, 2021; Javed, 2017, 2018; Javed, Aldalaien, et al, 2019). Figure 1 represents the general government’s final consumption expenditure for Oman.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have scrutinized the role of government expenses on the EG of the country (Aziz & Asadullah, 2017). However, the literature still lacks an efficient explanation of GE’s different dimensions on the EG in Oman’s particular context (Castaño et al, 2016; Husain & Javed, 2019a, 2019b; Husain et al, 2021; Javed, 2017, 2018; Javed, Aldalaien, et al, 2019). Figure 1 represents the general government’s final consumption expenditure for Oman.…”
Section: Introductionmentioning
confidence: 99%
“…They found out that the economy of Oman is far from being diversified and they put forward a model which will help the policymakers to study the influence of crude oil on other sectors. Husain and Javed (2019) They studied the effect of announcements on the listed companies in MSM 30.They found that the announcements have a significant effect on the price action of the companies.…”
Section: Author Findingsmentioning
confidence: 99%
“…Whether a return on equity is regarded as suitable will depend on what is standard for the industry or firm peers. A second problem that can create a high return on equity is surplus debt [11,25]. If a firm has been continuously borrowing, it can raise the return on equity as equity equals assets minus debt.…”
Section: Impacts Of Total Debt To Total Asset On Return On Equitymentioning
confidence: 99%